2022
DOI: 10.3390/jfmk7030068
|View full text |Cite
|
Sign up to set email alerts
|

Postural Assessment Systems in the Prevention of Haemophilic Arthropathy: A Narrative Review

Abstract: This narrative review aims to give an overview of some postural evaluation systems currently used in patients with haemophilia. Among them, first, we analyse the HJHS scale, recognized as a specific evaluation tool for haemophilic arthropathy. Second, we focus on other systems usually used in non-haemophilic patients that have also shown good applicability in this patient category, such as gait analysis, stabilometry, and baropodometric examination. This review underlines the use these tools could have in clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
2
0
0
Order By: Relevance
“…Results of the study presented herein also reveal a lower knee extension strength of both legs and a lower handgrip strength of both hands in PwH, supporting previous studies 7,23,24 . Besides, the SPPB sit to stand test, which indicates the subjects’ strength based functional ability in an everyday setting, showed that PwH perform this task in a slower pace.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results of the study presented herein also reveal a lower knee extension strength of both legs and a lower handgrip strength of both hands in PwH, supporting previous studies 7,23,24 . Besides, the SPPB sit to stand test, which indicates the subjects’ strength based functional ability in an everyday setting, showed that PwH perform this task in a slower pace.…”
Section: Discussionsupporting
confidence: 88%
“…This study aimed to provide information on objective functional mobil- .005 Results of the study presented herein also reveal a lower knee extension strength of both legs and a lower handgrip strength of both hands in PwH, supporting previous studies. 7,23,24 Besides, the SPPB function declines, which was also previously described for PwH. 27 Indeed, a vicious circle might occur as it is known that subjective physical performance negatively correlates with kinesiophobia, 28,29 which is also observed in the study presented herein (r s = −0.483).…”
Section: Discussionsupporting
confidence: 83%